The influence of vegetation on bird distribution in dry forests and oak woodlands of western Mexico - Corcuera, Pablo (2006)
he bird species distribution along a dry forest-oak woodland vegetation gradient was studied in autumn and spring in two consecutive years. Intra-seasonal comparisons showed that bird species had similar distributions in each of the two years. Inter-seasonal changes were mainly due to compositional differences even though resident species generally used similar habitats in both seasons. Ordination analyses, based on the first year bird species abundances, showed a clearly segregated distribution between forest and woodland birds. Within these two vegetation types, the distribution tended to be more individualistic. Nevertheless further habitats could be identified according to groups of birds having similar distributions. These habitats did not cor-respond to the plant associations which resulted from a previous classification of the vegetation. Observations of the plant use by the birds during the study period showed that, in most cases, the plant variables associated with ordination analyses are unlikely to be very important for the bird species life cycles.